Fatherhood Experiences in Adolescent Fathers - Zahra, Tamela; Puspitasari, Yeviza (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: Fathers, especially adolescent fathers, need support to face their new roles so that these roles can be carried out effectively. Without support, the mental health of the child, the mother, and even the father himself may be negativeky impacted, as well as the child’s growth, development, and the child’s social adaptation abilities.Aims: To review and map scientific evidence about the experience of fatherhood in adolescent fathersMethod: The design used in this research is a scoping review guided by the PRISMA-ScR checklist and uses the PICo framework.Results: Based on the 8 articles included in this scoping review, 3 themes were produced, namely the impact (change) of becoming a father at a teenage age, factors causing becoming a father at a teenage age, obstacles to becoming a father at a teenage age.Conclusion: Adolescent fatherhood is a shocking experience, and the unpreparedness and lack of information that adolescent fathers face can make them confused about their new role.